Azares, riscos e culpas: representações sobre os acidentes de trabalho da construção civil na imprensa portuguesa (1996-2017) - Monteiro, Bruno; Almeida, Carla Aurélia de (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In this text, we analyse how the current events in the Portuguese press construct and transform the representations of labour accidents in the construction sector. From an attachment to a plurality of perspectives, we seek to understand the discursive strategies mobilized here. On the basis of a corpus of 1218 news items collected in a trade union archive, we carried out, between 1996 and 2017, a sociological critique in combination with a semantic and pragmatic analysis of the speeches produced.